GE_GERICHTE C/4031/2015 vom 14. November 2016 - GE Cour de justice (2016)
BAIL À LOYER ; RÉSILIATION ; SOUS-LOCATION ; SOMMATION ; PRINCIPE DE LA RÉCEPTION ; PRINCIPE DE LA BONNE FOI | CO.257f.3; CO.271.1;